Analysis of the Effect of Psychosocial Factors on the Performance of Inpatient Nurses at Lasinrang Regional General Hospital, Pinrang Regency, Indonesia - Syafiuddin, Syamsurya; Suharni, Suharni; Gobel, Fatmah Afrianty (Postgraduate Program in Public Health, Universitas Muslim Indonesia, 2022)
Background:In the last decade, occupational psychosocial factors have become a major concern in occupational health. Changes that have occurred in the labor market, increased globalization, competition, flexibility, service sector development and new forms of work organization. The increasing prevalence of occupational psychosocial factors exposure to the working population. Method:This research is an analytic observational study with a cross sectional study approach. The research sample was 147 nurses who were determined by the total sampling method. Data were collected using a questionnaire and then analyzed by logistic regression test at a confidence level of 95% (x = 0.05). Results:The results of this study obtained that there is a significant effect between workload on performance (p value = 0.815) work stress on performance, (p value 0.094) interpersonal relationship on performance, (p value 0.058), responsibility for performance (p 0.001) . The multivariate result that has the most influence on performance is responsibility, because it has the largest p value, which is 0.001. Conclusion:Responsibility is a variable that greatly affects performance. The author suggests to the hospital to pay attention to the psychosocial factors of nurses at work.